The Women's Guide to Successful Investing Achieving Financial Security and Realizing Your Goals - Tengler, Nancy (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
It is no secret that women are increasingly controlling wealth. Estimates suggest that women control more than 50% of all wealth and growing. Importantly, 95% of women will be their family's primary financial decision maker at some point in their lives. Yet recent studies show that Millennial women are deferring financial and investing decisions at a greater pace than Baby Boomer women. Targeted to all women "with a clear recognition that though the objectives and needs of this vast segment may not necessarily be homogeneous, women share common challenges when it comes to investing, this book provides clear instruction and a series of Intelligent Investing Rules for women to live by, especially in these times with sticky and persistent inflation and rising interest rates. The Women's Guide to Successful Investing demonstrates how women can develop the knowledge and skills required to accumulate wealth and build an investment portfolio for the long term. Providing proven wealth accumulation strategies, tailored advice, and a comprehensive market analysis, this second edition is a must-read for female investors who want to master volatile markets with long-term success. Written by a female CEO, CIO, and investment manager whose career has spanned 38 years, the book offers a much-needed blueprint for investments for women. Nancy Tengler's career as a portfolio manager spans 40 years; she is currently the CEO and Chief Investment Officer of Laffer Tengler Investments. Nancy is a passionate advocate for women's financial literacy and she leads the firm's Women & Wealth initiative. Nancy is a sought-after TV and print financial commentator on local and national media outlets. She lives in Incline Village, NV with her 2 labs and hikes the Tahoe Trail daily. .
1 Wealth Accumulation Is an Attitude Investing for your future requires a few goals and much less capital than you think -- 2 Saving to Invest is the Best Strategy -- 3 COVID Hit Women's Finances Much Harder than Men's Women left the worforce en masse - at what cost? -- 4 It's True! Women Make Better Investors than Men (sorry guys) Women inherently display the traits required for successful investing -- 5 Developing an Intelligent Investing Strategy All Your Own Like any discipline, sound investing can become muscle memory for the diligent student and practitioner -- 6 Developing an Investment Discipline That Will Achieve our Goals-Continued: The Stock Market is a Tug of War between Fear and Greed; Arm Yourself with the Tools to Succeed -- 7 Construct Your Portfolio Like a Dinner Party Invitation List: Holdings Should Be Balanced and Behave Well If Things Get Out of Hand -- 8 Apple, Inc.-A Case Study in How to Select a Core Holding: A Role Model Investment You Will Want to Emulate -- 9 Mutual Funds Are So 1990, How to use Exchange-Traded Funds To Round Out Your Portfolio Holdings. To Crypto or not to Crypto and what the heck are meme stocks? -- 10 A Case Study of a Fallen Consumer Discretionary, Tech, E-commerce Company: Amazon. And Stocks to Own for a Lifetime -- 11 Five Critical Lessons and Warnings: Don't Touch a Hot Stove, Don't Talk to Strangers and Other Lessons for the Ages -- 12 Twelve Intelligent Investing Rules - And One More for Good Measure: Rules for Women to Invest By.
Keywords: Financial services industry; Valuation; Financial risk management; Economics -- Psychological aspects; Financial Services; Investment Appraisal; Risk Management; Behavioral Finance